High psychological stress levels related to delivery can increase the occurrence of postpartum mental disorders - Sun, Ruixue; Zhao, Mingzhe; Ma, Liangkun; Duan, Yanping; Wei, Jing (Frontiers in Psychiatry, 2023)
Objective: The study sought to explore the relationship between high psychological stress levels related to delivery and postpartum mental disorders.Methods: A total of 284 parturients were included in the study from July 2021 to January 2022. The stress level at one month postpartum was assessed by the Impact of Event Scale-Revised (IES-R). Parturients with an IES-R score ≤ 9 were included in the low psychological stress level group, and those with an IES-R score > 9 were included in the high psychological stress level group. The Edinburgh Postnatal Depression Scale (EPDS), Union Physio-Psycho-Social Assessment Questionnaire (UPPSAQ-70), Symptom Checklist-90 (SCL-90) and Mini-International Neuropsychiatric Interview (M.I.N.I.) were conducted at 42±7 days postpartum to assess the mental health of parturients.The parturients' mental health after birth was assessed by the EPDS, UPPSAQ-70, and SCL-90. Semi-structured diagnostic interviews were conducted at 42±7 days postpartum by using the M.I.N.I.Results: The incidence rate of postpartum mental disorders was 20.42% (58/284), the incidence rates of postpartum depression, anxiety disorders, obsessive-compulsive disorder and posttraumatic stress disorder were 17.96% (51/284), 11.97% (34/284), 4.58% (13/284) and 1.41% (4/284), respectively, and the comorbidity rate was 58.62% (34/58). A history of mental disorders and pregnancy complications were risk factors for postpartum depression (P=0.028, P=0.040, respectively); a history of mental disorders, a lack of physical exercise, partner violence and pregnancy complications were risk factors for postpartum anxiety disorders (P=0.003, P=0.007, P=0.031, P=0.048, respectively); and the delivery of female infants was a risk factor for postpartum obsessive-compulsive disorder (P=0.022).The risk of postpartum depression, anxiety disorders and obsessive-compulsive disorder was 9.125 times (95% CI= 3.900~21.349, P<0.01), 7.310 times (95% CI=2.588~20.649, P<0.01) and 6.259 times (95% CI=1.347~29.093, P<0.01) higher in postpartum women with high psychological stress levels related to delivery than in those with low psychological stress levels, respectively.Conclusions: The incidence of postpartum mental disorders is high and has a positive correlation with the level of psychological stress. This may lead to a new perspective of the effect of psychological stress on postpartum mental disorders and attract more attention to other mental disorders in addition to postpartum depression.